Right ventricular function during orthotopic liver transplantation: three-dimensional transesophageal echocardiography and thermodilution - Rosendal, Christian; Almamat uulu, Keneshbek; De Simone, Raffaele; Wolf, Ivo; Deckert, Andreas; Martin, Eike; Böttiger, Bernd W.; Rauch, Helmut (Annals of transplantation, 2012)
Background: Right ventricular (RV) function is an important aspect of anesthesia management during orthotopic liver transplantation (OLT). Because of its geometrical complexity, assessment of RV dimensions with transesophageal echocardiography (TEE) is a difficult task. The aim of this prospective single-site study was to investigate the feasibility of intraoperative assessment of RV parameters based on reconstructive three-dimensional (3D) TEE and to compare the measurements to thermodilution-derived values acquired with a modified pulmonary artery catheter. Material/Methods: Measurements were performed at four different time points during 30 OLT with 3D-TEE. At the same time comparative values of RV parameters were acquired with a fast-response thermistor pulmonary artery catheter. Results: 3D reconstruction was feasible in all patients. RV dimensions measured with 3D-TEE averaged 119.4ml (±38.5 ml) for enddiastolic and 68.9 ml (±27.7 ml) for endsystolic volumes. The RV ejection fraction was 42.2% (±9.3%). The volumes obtained by thermodilution were 263.7 ml (±64.5 ml) enddiastolic and 159.3 ml (±47.5 ml) endsystolic, both significantly greater than by 3D-TEE, and the ejection fraction was found to be 39.5% (±8.4%). No correlation was found between the volumes or the function determined by either method. Conclusions: Reconstructive 3D-TEE is a viable technique during OLT and leads to plausible RV parameters. However, no correlation was found with simultaneous measurements or parameters performed with thermodilution. However, based on our data cardiac output measurements by thermodilution appear reasonable. Due to both lack of agreement with 3D-TEE and extraordinary high RV volumes the question about the most valuable monitoring technique of RV dimensions and function during OLT can not finally be answered.
Gesehen am 23.04.2018